Multiproduct Intermediaries - Rhodes, Andrew; Watanabe, Makoto; Zhou, Jidong (Journal of Political Economy, 2021)
This paper develops a new framework for studying multiproduct intermediaries when consumers demand multiple products and face search frictions. We show that a multiproduct intermediary is profitable even when it does not improve consumer search efficiency. The intermediary optimally stocks high-value products exclusively to attract consumers to visit and then profits by selling nonexclusive products that are relatively cheap to buy from upstream suppliers. Relative to the social optimum, the intermediary tends to be too big and stock too many products exclusively. We use the framework to study the design of shopping malls and the impact of direct-to-consumer sales by upstream suppliers on the retail market.